2017
DOI: 10.1080/2162402x.2017.1290037
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab-mediated high-affinity ligation of FcγRIIIA/CD16 primes NK cells for IFNγ production

Abstract: Natural killer (NK) cell-mediated antibody-dependent cellular cytotoxicity (ADCC), based on the recognition of IgG-opsonized targets by the low-affinity receptor for IgG FcγRIIIA/CD16, represents one of the main mechanisms by which therapeutic antibodies (mAbs) mediate their antitumor effects. Besides ADCC, CD16 ligation also results in cytokine production, in particular, NK-derived IFNγ is endowed with a well-recognized role in the shaping of adaptive immune responses.Obinutuzumab is a glycoengineered anti-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 57 publications
5
45
0
Order By: Relevance
“…Following CD16A engagement, we observed a transient impaired function in CD16A-dependent as well as "natural" NK cell cytotoxicity and IFNg expression toward tumor cells. The impairment of CD16A-dependent activity may be explained by the nearly complete loss of CD16A expression upon CD16A engagement, which, at least in part, involved matrix metalloproteinase-mediated cleavage, consistent with previous studies, or receptor internalization, as additionally described (24,28,(41)(42)(43). The transient lower responsiveness in "natural" NK cell antitumor reactivity toward K562 cells suggested a desensitization of other NK cell-activating receptors, such as NKp30 and NKG2D, that have previously been shown to be involved in K562 lysis (44,45).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Following CD16A engagement, we observed a transient impaired function in CD16A-dependent as well as "natural" NK cell cytotoxicity and IFNg expression toward tumor cells. The impairment of CD16A-dependent activity may be explained by the nearly complete loss of CD16A expression upon CD16A engagement, which, at least in part, involved matrix metalloproteinase-mediated cleavage, consistent with previous studies, or receptor internalization, as additionally described (24,28,(41)(42)(43). The transient lower responsiveness in "natural" NK cell antitumor reactivity toward K562 cells suggested a desensitization of other NK cell-activating receptors, such as NKp30 and NKG2D, that have previously been shown to be involved in K562 lysis (44,45).…”
Section: Discussionsupporting
confidence: 88%
“…PKC activation can mediate IFNg production and is important for K562 lysis but dispensable for ADCC, which, in turn, requires PI3K activation (48,49). The observed impairment in our study after 20-hour exposure to AFM13 or rituximab may exceed the inhibitory effect of shortterm (1.5-hour) CD16A engagement, which was reported to not affect IFNg production or responsiveness to PMA/ionomycin, while resulting in defective degranulation due to SHP-1 recruitment, inhibition of PLCg2/Vav-1/SLP-76 phosphorylation, and both FceR1g and CD3z degradation (42,43,50).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Fc-engineered antibodies with improved affinity to FcγRIIIa show higher therapeutic efficacy relative to native Fc because they are capable of priming and activating NK cells more efficiently 14,15 . However, several studies showed that although the depletion of NK cells or neutrophils did not significantly reduce tumor suppression activity, exhaustion of macrophages abrogated the Fig.…”
Section: Fc Receptors: Fcγ Receptors (Fcγrs) and Neonatal Fc Receptormentioning
confidence: 99%
“…Obinutuzumab (GA101) is a type II anti-CD20 mAb with enhanced direct cell death activity and a glycoengineered Fc region that enhances its binding affinity to FcgRIIIa on NK and other effector cells, thereby resulting in stronger ADCC compared with rituximab (11)(12)(13)(14). Such high affinity ligation of FcgRIIIa has been shown to prime NK cells for IFNg production (15).…”
Section: Introductionmentioning
confidence: 99%